The Diagnosis of Genital Herpes – Beyond Culture: An Evidence-Based Guide for the Utilization of Polymerase Chain Reaction and Herpes Simplex Virus Type-Specific Serology. Issue 4 (2007) - Ratnam, S; Severini, A; Zahariadis, G; Petric, M; Romanowski, B
Abstract : Accurate identification of persons with genital herpes is necessary for optimal patient management and prevention of transmission. Because of inherent inaccuracies, clinical diagnosis of genital herpes should be confirmed by laboratory testing for the causative agents herpes simplex virus type 1 (HSV-1) and HSV type 2 (HSV-2). Further identification of the HSV type is valuable for counselling on the natural history of infection and risk of transmission. Laboratory methods include antigen detection, culture, polymerase chain reaction (PCR) and conventional and type-specific serology (TSS). PCR has, by far, the greater sensitivity and should be the test of choice for symptomatic cases. HSV-2 TSS is indicated for patients with genital lesions in whom antigen detection, culture or PCR fail to detect HSV, and for patients who are asymptomatic but have a history suggestive of genital herpes. HSV-2 TSS is further indicated for patients infected with HIV. HSV-2 TSS along with HSV-1 TSS may be considered, as appropriate, in evaluating infection and/or immune status in couples discordant for genital herpes, women who develop their first clinical episode of genital herpes during pregnancy, asymptomatic pregnant women whose partners have a history of genital herpes or HIV infection, and women contemplating pregnancy or considering sexual partnership with those with a history of genital herpes. The above should be performed in conjunction with counselling of infected persons and their sex partners.